Design and fabrication of two kind of SOI-based EA-type VOAs. (June 2018) - Yuan, Pei; Wang, Yue; Wu, Yuanda; An, Junming; Hu, Xiongwei
Highlights: Electro-absorption VOAs with two different structures are demonstrated. The advantage of the series VOA in electrical performance is proved. The series VOA reached a high attenuation efficiency among all demonstrated EA VOAs. The theoretical explanation to the high power consumption of the series VOA is given. The response time of the series VOA is in tens of nanosecond scale. Abstract: SOI-based variable optical attenuators based on electro-absorption mechanism are demonstrated in this paper. Two different doping structures are adopted to realize the attenuation: a structure with a single lateral p-i-n diode and a structure with several lateral p-i-n diodes connected in series. The VOAs with lateral p-i-n diodes connected in series (series VOA) can greatly improve the device attenuation efficiency compared to VOAs with a single lateral p-i-n diode structure (single VOA), which is verified by the experimental results that the attenuation efficiency of the series VOA and the single VOA is 3.76 dB/mA and 0.189 dB/mA respectively. The corresponding power consumption at 20 dB attenuation is 202 mW (series VOA) and 424 mW (single VOA) respectively. The raise time is 34.5 ns (single VOA) and 45.5 ns (series VOA), and the fall time is 37 ns (single VOA) and 48.5 ns (series VOA).